Perbandingan Metode Activity Based Costing (ABC) Dalam Menghitung Harga Pokok Produksi Pada UMKM Kopi Harum Manis - Abizar, Muhammmad; Rafli, Muhammad; Istiaji, Agung (CV Warnak Johanna Nusantara, 2025)
Accurate determination of cost of goods manufactured (COGS) is a vital aspect in the success of MSMEs because it directly affects the determination of selling prices and profit. This study aims to compare the accuracy of COGS calculations between the traditional method and the Activity Based Costing (ABC) method at MSME Kopi Harum Manis. The traditional method distributes costs based on output volume, while ABC allocates costs based on the consumption of relevant activities using cost drivers. This study uses a quantitative descriptive approach with primary and secondary data from activities and financial reports for the period March 2025. The results show that the ABC method produces lower COGS and reflects more realistic cost consumption than the conventional method. This difference shows that the application of the ABC method provides more accurate cost information, prevents distortion of overhead allocation, and can be used as a basis for strategic decision making in pricing and increasing production efficiency in MSMEs